Compensation Relationships in the Solvation Thermodynamics of Proton Acceptors in Aliphatic Alcohols - Boris N. Solomonov; Mansur B. Khisamiev; Mikhail I. Yagofarov (Liquids, 2025)
Solvent association and solute–solvent complexation are known to influence the relationship between the thermodynamic functions of solvation, known as the compensation relationship. Here, we accomplish a series of works devoted to the analysis of Gibbs energy–enthalpy relations in the systems with different capabilities of hydrogen bonding. The data on proton acceptors solvated in alcohols were collected, and the quantitative regularities in their solvation thermodynamics were established, depending on the binding degree in solution. The equations connecting the Gibbs energies and enthalpies of solvation in the systems with competition for hydrogen bonding sites were derived from the previously found correlation between the thermodynamic functions of complexation and solvation in simpler solutions. These equations enabled the successful prediction of the solvation enthalpies of 56 proton acceptors in alcohols (RMSD = 1.8 kJ·mol−1). Together with the results of the previous works, the general linear equation connecting the Gibbs energies and enthalpies of solvation in various solute–solvent systems has been obtained. This finding led us to reshaping common understanding of the compensation relationship phenomenon.